Effect of ferrule preparation on fatigue resistance of teeth restored with quartz-fiber posts - Nasermostofi Sh; Raghanians A.; Banava S.; Jalalian E.; Abdollah A. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: A key factor in restoring the endodontically treated teeth is ferrule preparation. When the ferrule is absent, occlusal loads may cause the post or root to fracture. The purpose of this in vitro study was to evaluate the effect of ferrule preparation on fatigue resistance of teeth restored with quartz-fiber posts. "nMaterials and Methods: Twenty single-rooted lower premolars having similar dimentions were randomly devided into two groups of 10. In control group the teeth were prepared with 3-mm of remaining coronal tooth structure and in test group teeth were prepared with 1-mm of remaining coronal tooth structure. The teeth were endodontically treated. 9-mm long Post holes were prepared, and D.T. light quartz-fiber(RTD,France) posts were cemented with Panavia F2(Kuraray,Japan).Then the core build up was done with Bisco core build up composite(Bisco,USA) and full metal crowns were cemented with Zinc phosphate(Harvard cement, Germany). All specimens were mounted in acrylic resin blocks and intermittently loaded (180 N) at an angulation of 45- degree to the long axis of the teeth at a frequency of 4 loads per second, until failure occurred. "nResults: There was significant difference between the loads cycles of two groups studied. (p<0.0001). "nConclusion: The results of this study showed that an increased amount of coronal dentin significantly increases the fracture resistance of teeth restored with quartz-fiber posts.